Substantiation of the Effectiveness of Water-Soluble Hydrophobic Agents on the Properties of Cement Composites - Jakub Hodul; Tatiana Beníková; Rostislav Drochytka (Buildings)
This paper aims to verify the effect of water-soluble hydrophobisations on cementitious composites such as concrete (S1) and cement-bonded particle boards (S2). The research was focused on the water-soluble hydrophobisations based on methylsilanolate (MS), a mixture of silanes and siloxanes (SS) and alcohol with the addition of nano-silica (N). The results provide a comprehensive overview of the benefits and effectiveness of water-soluble hydrophobisations in the context of building materials, outlining a direction towards the development of new, more environmentally friendly solutions in the construction industry. For this reason, alternative raw materials (brick recyclate and brick dust) were used for S1 substrate preparations. How the water-soluble hydrophobisations, including hydrophobisations with the addition of nano-silica (N), affect the process of water evaporation during hydration and the resulting water repellence of the S1 and S2 substrates were experimentally verified through a series of tests, e.g., measurement of the contact angle and depth of water penetration under pressure. The evaluation of the effect of hydrophobisations on the resistance of substrate to aggressive gaseous and liquid environments was observed by the determination of the resistance to carbonation and sulphation processes and the resistance of the concrete to aggressive liquid media (10% H2SO4, 10% CH3COOH). Although the hydrophobisations did not have a significant effect on some aspects of S1, such as the resistance to carbonation and sulphate attack, improvement was observed in other areas, such as the quadrupling increase in contact angle of the surface and 9 mm decrease in water pressure penetration into the concrete substrate.